Ivar Kreugar's Contribution to U.S. Financial Reporting. - Flesher, Dale L.; Flesher, Tonya K. (The Accounting Review, 1986)
ABSTRACT: The most widely-held securities in America (and also the world during the 1920s were the stocks and bonds of Kreuger & Toll, Inc., a Swedish match conglomerate. The company was founded and headed by Ivar Kreuger. The reason Kreuger's securities were so popular was that they were sold in small denominations and paid high dividends. Dividends of over 20 percent annually were paid on both stocks and bonds. Unfortunately, these dividends were paid mostly out of capital, not profits. Kreuger was essentially operating a giant pyramid scheme, which was hidden from the investing public by Kreuger's insistence that financial statements not be audited. He preached a philosophy that secrecy was paramount to corporate success. The bankruptcy of the company in 1932 was the largest on record and resulted in numerous changes in financial reporting. Articles in magazines and newspapers kept Americans aware of the extent of the fraud scheme at the same time Congress was considering the passage of a federal securities law. Thus, the timing of the bankruptcy and the corresponding media coverage made it politically expedient to pass laws that would make it difficult for similar schemes to be successful in the future. Such laws were indeed passed, and the Congressional committee reports specifically refer to Kreuger. The hypothesis of this paper is that the Ivar Kreuger fraud contributed significantly to the passage of the securities acts.